A methodological study on the combination of qualitative and quantitative methods in cognitive interviewing for cross‐cultural adaptation. Issue 1 (30th October 2021) - Jia, Miao; Gu, Yao; Chen, Yanhua; Tu, Jinyi; Liu, Yue; Lu, Huiqi; Huang, Simin; Li, Jinjun; Zhou, Hongzhen
Abstract: Aim: The aim of this study is to explore the use of the Questionnaire Appraisal System with a combination of qualitative and quantitative methods in cognitive interviewing for cross‐cultural adaptation. Design: This is a descriptive methodological study. Methods: Using the Mandarin version of the Post‐Stroke Checklist as an example, cognitive interviews were conducted with 27 stroke survivors in Guangzhou between November 2020 and February 2021. The Questionnaire Appraisal System was applied as a codebook in focus group discussions to perform quantitative data collections and quantitative content analysis. Results: Thirty‐eight problems were proposed in focus group discussions and identified all but four of the 30 questions that emerged in the cognitive interviews. A new item was added to the Questionnaire Appraisal System for better categorization. Four categories and six subcategories of problems in the checklist were revealed.